Identification of a transmissible plasmid from an Argentine Sinorhizobium meliloti strain which can be mobilised by conjugative helper functions of the European strain S. meliloti GR4 - Pistorio, Mariano (2003)
We describe in this work the identification and the conjugal properties of two cryptic plasmids present in the strain Sinorhizobium meliloti LPU88 isolated from an Argentine soil. One of the plasmids, pSmeLPU88b (22 kb), could be mobilised from different S. meliloti strains to other bacteria by conjugation only if the other plasmid, pSmeLPU88a (139 kb), was present. This latter plasmid, however, could not be transferred via conjugation (frequency <10-9 transconjugants per recipient) contrasting with the conjugal system from the previously described strain GR4, where one plasmid is mobilisable and a second one (helper) is self-transmissible. Despite the differences between the two systems, the conjugative helper functions present in the cryptic plasmids of strain GR4 were active in the mobilisation of plasmid pSmeLPU88b from strain LPU88. Contrasting with this, plasmid pSmeLPU88b was not mobilised by the helper functions of the broad-host-range plasmid RP4. Eckhardt gel analysis showed that none of the plasmids from strain GR4 were excluded in the presence of plasmid pSmeLPU88b suggesting that they all belong to different incompatibility groups for replication. The small plasmid from strain LPU88, pSmeLPU88b, was only able to replicate in members of the Rhizobiaceae family such as Rhizobium leguminosarum, Rhizobium tropici and Agrobacterium tumefaciens, but not in Escherichia coli or Pseudomonas fluorescens. The observation suggests that most likely plasmid pSmeLPU88b was not received from a phylogenetically distant bacterium.